2011
DOI: 10.1007/s00396-011-2573-y
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior of isotactic polypropylene induced by competition action of β nucleating agent and high pressure

Abstract: Addition of β-form nucleating agent (β-NA) to isotactic polypropylene (iPP) can greatly induce the variation of the crystallization of matrix. Here, we introduce high pressure to the crystallization process of β-NA nucleated iPP. It is observed that there is a competition between the effect of high pressure and the nucleation effect of β-NA on crystallization of iPP. With the increasing of high pressure, both the contents of β-iPP and α-iPP decrease while the content of γ-iPP increases. A novel crystalline mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
(71 reference statements)
2
12
0
Order By: Relevance
“…Only few articles have considered the respective effects of high pressure and β-nucleating agents [ 44 , 58 ]. Obadal et al [ 44 ] have tested NU 100 ( N , N ′-dicyclohexylnaphthalene-2,6-dicarboxamide) as β-nucleant and concluded that it enhances the formation of the β-phase at lower P and also at high P but at low T .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few articles have considered the respective effects of high pressure and β-nucleating agents [ 44 , 58 ]. Obadal et al [ 44 ] have tested NU 100 ( N , N ′-dicyclohexylnaphthalene-2,6-dicarboxamide) as β-nucleant and concluded that it enhances the formation of the β-phase at lower P and also at high P but at low T .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yang et al [ 58 ] have also used another very efficient commercial β-nucleant: TMB-5, an aryl amide derivative, which has a chemical structure similar to NU 100. Some of their results are similar to ours, i.e., an increase of the γ content and a decrease of the β content with increasing P .…”
Section: Discussionmentioning
confidence: 99%
“…The crystallographic planes for phase of all the films corresponding to (110), (040), and (130) lattice planes, ascribe to diffraction peaks at 2 around 14.3 , 16.8 , and 18.4 , respectively can be seen in Fig.5 [22][23][24]. The composite films with 1.0 phr CaCO 3 , 1.5 phr CaCO 3 , 1.0 phr modified CaCO 3 , and 1.5 phr modified CaCO 3 presented diffraction peak at 2 around 16.0 refer to the phase (300) [23][24][25]. It has revealed that the addition of modified CaCO 3 was higher phase peak than the addition of CaCO 3 .…”
Section: X-ray Diffractionmentioning
confidence: 98%
“…Obadal et al proposed that aryl amide derivative (a kind of β-NA) enhanced the formation of the γ-iPP during isothermal crystallization at a lower pressure or at a high pressure but low temperature [31]. Yang et al reported an increase in γ-iPP and a decrease in β-iPP with increasing pressure in iPP nucleated with aryl amide derivative, and they found γ-iPP could grow on the lateral of the β-NA needlelike structure and attributed it to the dual nucleation effects of β-NA [32]. However, Sowinski et al reported that calcium pimelate, another typical kind of β-NA, only has a slight effect on the crystallization of γ-iPP under a high pressure [33].…”
Section: Introductionmentioning
confidence: 99%